The Role of Courts in Addressing Social Inequality - Dikrurahman, Diki (Journal of Law and Social Politics, 2025)
Social inequality remains a persistent global issue, manifesting in various forms such as economic disparity, racial discrimination, gender bias, and unequal access to justice. The judiciary plays a crucial role in mitigating these inequalities by interpreting and enforcing laws that promote social justice. This study aims to examine the extent to which courts influence social equity through landmark rulings, judicial activism, and policy enforcement. This research employed a qualitative approach, utilizing doctrinal legal analysis and case study methodology to assess key judicial decisions from different jurisdictions over the past five years. By analyzing court rulings, legislative interpretations, and the impact of judicial decisions on marginalized communities, this study explores the effectiveness of courts in addressing systemic disparities. The findings indicate that courts have played a pivotal role in advancing social justice, particularly in areas such as civil rights, labor law, and environmental justice. However, limitations exist due to political influences, institutional constraints, and inconsistent enforcement mechanisms. The study also highlights the necessity for a more proactive judicial approach and collaborative governance to ensure sustainable social change. In conclusion, while courts serve as essential instruments for promoting equality, their effectiveness depends on broader systemic support, including legal frameworks, public policy, and civic engagement. This research contributes to the ongoing discourse on judicial intervention in social justice by providing insights into best practices and challenges in leveraging the legal system for equitable reform.